2012
DOI: 10.4028/www.scientific.net/ddf.323-325.503
|View full text |Cite
|
Sign up to set email alerts
|

The Solubility of Indium in Liquid Gallium Supercooled to 12 K

Abstract: The method of perturbed angular correlation (PAC) was used to determine lattice locations of 111 In impurity probe atoms present in extreme dilution in the intermetallic compound FeGa 3 . In slightly Ga-poor samples, probes were found to strongly prefer one of two inequivalent Ga-sites. In slightly Ga-rich samples at room temperature, 293 K, the PAC spectrum exhibited an unperturbed quadrupole interaction signal that is consistent with indium probes dissolved in small liquid pools of the excess Ga. A myriad o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
(21 reference statements)
2
3
0
Order By: Relevance
“…Second, the results also show that the probe nuclei in these “pools” of metallic Zn trapped between the grains of ZnO sense quadrupole interactions typical of textured materials with a preferential direction. The same phenomenon was observed in ZnO microtubes decorated with shorter nanowires and reported by Rivaldo-Gómez et al The work reported by Yin et al describes a similar situation for 111 In­( 111 Cd) in metallic gallium. , …”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Second, the results also show that the probe nuclei in these “pools” of metallic Zn trapped between the grains of ZnO sense quadrupole interactions typical of textured materials with a preferential direction. The same phenomenon was observed in ZnO microtubes decorated with shorter nanowires and reported by Rivaldo-Gómez et al The work reported by Yin et al describes a similar situation for 111 In­( 111 Cd) in metallic gallium. , …”
Section: Resultssupporting
confidence: 81%
“…The same phenomenon was observed in ZnO microtubes decorated with shorter nanowires and reported by Rivaldo-Goḿez et al 13 The work reported by Yin et al describes a similar situation for 111 In( 111 Cd) in metallic gallium. 43,44 Since XRD measurements do not reveal the presence of Zn, the occurrence of metallic Zn observed by PAC, which certainly has an influence on transport properties, may be in the form of very thin layers trapped between ZnO grains. The difference in detecting the metallic Zn between both techniques can be ascribed to the local character of PAC that is able to observe the environment around the probe nuclei within an atomic range.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…An X-ray diffraction measurement of one of the Ga-rich samples showed only the FeGa 3 phase, so any Ga metal present must have had a small volume fraction. It would therefore appear that In strongly segregates from FeGa 3 to the liquid Ga phase, which is consistent with other recent PAC studies that show In has a high affinity for liquid Ga [31,32,33].…”
Section: Ga-rich Samplessupporting
confidence: 91%
“…35 The occurrence of this phase-separation phenomenon can be attributed to the fact that the solubility of In within Ga is very low (<3.5%) at such a low temperature and, therefore, precipitation of In occurs to form a solid particle. 36 Due to the instant and nearly full separation between In and Ga phases, the size of the In core is independent of temperature and is determined by the concentration of In within the alloy only.…”
Section: Resultsmentioning
confidence: 99%